Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/cmar.s216034
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictive Role Of Body Composition Parameters In Operable Breast Cancer Patients Treated With Neoadjuvant Chemotherapy</p>

Abstract: Background: Fat tissue is strongly involved in BC tumorigenesis inducing insulin resistance, chronic inflammation and hormonal changes. Computed tomography (CT) imaging instead of body mass index (BMI) gives a reliable measure of skeletal muscle mass and body fat distribution. The impact of body composition parameters (BCPs) on chemosensitivity is still debated. We examined the associations between BCPs and tumor response to neoadjuvant chemotherapy (NC) in patients treated for operable breast cancer (BC). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
(22 reference statements)
1
10
1
Order By: Relevance
“…Our previous study showed that increased amount and lower quality of VAT was associated with shorter distant disease-free survival via increasing insulin resistance [ 9 ]. Many other preclinical and clinical studies have reported a positive relationship between increased VAT, poor NACT outcome [ 18 ], and shorter survival outcome [ 9 , 10 ]; however, recent studies have indicated that deep abdominal SAT (daSAT)—defined as adipose tissue at the deepest layer of abdominal SAT—is also metabolically active and has a similar metabolic function to that of VAT. A clinical study showed that the depth of daSAT was a strong predictor of insulin resistance [ 19 ], as well as increased expression of pro-inflammatory, lipogenic, and lipolytic genes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that increased amount and lower quality of VAT was associated with shorter distant disease-free survival via increasing insulin resistance [ 9 ]. Many other preclinical and clinical studies have reported a positive relationship between increased VAT, poor NACT outcome [ 18 ], and shorter survival outcome [ 9 , 10 ]; however, recent studies have indicated that deep abdominal SAT (daSAT)—defined as adipose tissue at the deepest layer of abdominal SAT—is also metabolically active and has a similar metabolic function to that of VAT. A clinical study showed that the depth of daSAT was a strong predictor of insulin resistance [ 19 ], as well as increased expression of pro-inflammatory, lipogenic, and lipolytic genes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the relationship between SAT, VAT, MT and chemotherapy response rather than investigating the relationship between the BMI and chemotherapy response. Although there are many studies comparing these parameters with patient prognosis, a few studies investigated the response to chemotherapy with some of these parameters [ 15 , 16 , 25 ]. Although Iwase et al found that high VAT was associated with poor NAC outcomes in breast cancer patients especially in postmenopausal patients, they could not find any association between body composition parameters and pCR [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our patient numbers are similar, this difference may be due to different chemotherapy regimens and different distribution of patients among different receptor subtypes. Omarini et al published a recent study, which suggested a negative predictive role of visceral fat in tumor response to NAC [ 16 ]. VAT seemed to be more biologically active and with more procancerous activity than SAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate evaluation of patients’ nutritional status in metastatic setting cannot ignore the assessment of skeletal muscle mass and skeletal muscle density using computed tomography scan. Previous studies in various types of cancer highlighted the strong association between survival, treatment toxicities and the amount of muscle and adipose tissue at diagnosis such as its modification during chemotherapy [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%